Exopolysaccharides from yoghurt fermented by Lactobacillus paracasei: Production, purification and its binding to sodium caseinate. (May 2020) - Li, Xiao-Wei; Lv, Shun; Shi, Tian-Tian; Liu, Kang; Li, Qiang-Ming; Pan, Li-Hua; Zha, Xue-Qiang; Luo, Jian-Ping
Abstract: Lactobacillus paracasei that could release exopolysaccharide (EPS), was used as starter to prepare yoghurt under optimal fermented conditions. It was found that the viscosity of yoghurt increased exponentially with EPS production, and to elucidate this phenomen, the binding of EPS-S11 extracted and purified from yoghurt to casein was evaluated by turbidity and particle size analysis, zeta potential study, confocal laser scanning microscopy (CLSM) imaging, and isothermal titration calorimetry (ITC) determination. Results indicated that EPS-S11 with an average molecular weight of 1.68 × 10 7 Da, was mainly composed of mannose, glucose, galactose and glucuronic acid in a molar ratio of 0.87:0.92:1:0.24. Upon the addition of EPS-S11, the turbidity and particle size of casein solution both decreased in a dose-dependent manner, while the zeta potential was dose-dependently increased, suggesting that EPS-S11 might inhibit the aggregation of casein and thus enhanced its stability. ITC titration and CLSM imaging confirmed the existence of interactions between EPS-S11 and casein, which mainly involved in electrostatic interaction as well as hydrophobic interaction. Graphical abstract: The exopolysaccharide (EPS-S11) is an important factor required for the textural formation of yoghurt fermented by Lactobacillus paracasei . Image 1 Highlights: Lactobacillus paracasei could release exopolysaccharide into yoghurt. Fermentation conditions of yoghurt were optimized. Structural features of purified exopolysaccharide were studied. Interactions between exopolysaccharide and casein were investigated. Results indicated exopolysaccharide enhanced yoghurt texture.